Lithium battery negative electrode binder of modified carboxymethyl cellulose lithium

By grafting acrylic acid and sulfonic acid monomers on carboxymethyl cellulose, and introducing cystine and 2-(3,4-dihydroxyphenyl)ethylamine, modified carboxymethyl cellulose lithium is obtained, which solves the problem of stress caused by volume expansion during the circulation of silicon-based anode materials, and improves the cycle stability and overall performance of lithium-ion batteries.

CN119955444AActive Publication Date: 2025-05-09CHANGSHU WEIYI TECH

Patent Information

Application Number
CN202510444026.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-10
Publication Date
2025-05-09
Estimated Expiration
2045-04-10

AI Technical Summary

Technical Problem

In existing lithium-ion batteries, the silicon-based negative electrode material generates stress due to volume expansion during circulation, resulting in attenuation of battery capacity, and the adhesive is prone to failure during charging and discharging, affecting battery performance.

Method used

Modified carboxymethyl cellulose lithium is prepared by grafting the acrylic monomer and sulfonic acid monomer on the carboxymethyl cellulose backbone, and introducing cystine with disulfide bonds as the crosslinking agent, and 2-(3,4-dihydroxyphenyl)ethylamine with catechol groups as the tackifier, thereby improving its bonding properties and toughness.

Benefits of technology

Modified carboxymethyl cellulose lithium not only improves the bonding capacity and circulation performance with the silicon negative electrode, but also enhances the overall performance of the battery, including improving the specific capacity and circulation efficiency, and reducing the diffusion path of lithium between the electrodes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119955444A_ABST
    Figure CN119955444A_ABST
Patent Text Reader

Abstract

The invention discloses a lithium battery negative electrode binder of modified carboxymethyl cellulose lithium, and belongs to the technical field of lithium ion batteries, and the modified carboxymethyl cellulose lithium is prepared by grafting carboxymethyl cellulose with an acrylic monomer and a sulfonic monomer, acidifying, lithiating, cross-linking with cystine, and carrying out surface modification with 2-(3, 4-dihydroxyphenyl) ethylamine. The preparation method comprises the following steps: grafting an acrylic monomer and a sulfonic monomer copolymerization long chain on a main chain of carboxymethyl cellulose, introducing additional carboxyl and sulfonic groups, and introducing cystine with a disulfide bond as a cross-linking agent and 2-(3, 4-dihydroxyphenyl) ethylamine with a catechol group as a tackifier to prepare modified carboxymethyl cellulose lithium; the lithium content of the obtained modified lithium carboxymethyl cellulose is higher than that of common lithium carboxymethyl cellulose, the adhesive property is enhanced, the toughness is improved, and the cycle performance is enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium ion batteries, and in particular relates to a modified lithium carboxymethyl cellulose lithium negative electrode binder for lithium batteries. Background Art

[0002] Commercial lithium-ion batteries generally use graphite as the negative electrode material, but its theoretical capacity is only , which when applied to electric vehicles can only provide The energy density of silicon is very high ( ), the voltage for lithium ion deintercalation reaction is only 0.4V, and the natural reserves are abundant, the mining and processing technology is mature, and it is non-toxic and environmentally friendly. It is expected to replace graphite as the next generation of lithium ion battery negative electrode material. However, the commercial application of silicon-based negative electrode materials still needs to solve the 300% volume expansion during the cycle (lithiation process generates Li 15 Si4) problem.

[0003] Binders are crucial auxiliary functional materials in lithium-ion batteries. Their primary function is to bond the active materials, conductive agents, and current collectors together. This bonding ensures a cohesive connection between the materials and prevents the active materials from decomposing due to chemical and mechanical stresses during continuous charging and discharging. Furthermore, binders play a key role in forming a continuous electronic network, facilitating efficient electron and ion pathways, reducing the battery's internal resistance, and promoting good electronic and ionic conductivity within the battery. Therefore, binders play a vital role in improving the overall performance of lithium-ion batteries.

[0004] At present, oil-based binders represented by polyvinylidene fluoride (PVDF) and water-based binders represented by styrene-butadiene rubber (SBR) emulsion / carboxymethyl cellulose (CMC) are the two most widely used types of binders in commercial applications. Biomass-derived CMC binders contain polar functional groups, such as hydroxyl and carboxylic acid groups, which can form strong interactions with active materials or current foils through dipole-dipole interactions or secondary valence forces. From a mechanical point of view, CMC chains are hard and brittle, but early studies have shown that CMC is a very suitable binder for silicon-based negative electrodes. When CMC is used alone as a binder for silicon-based negative electrodes, the battery cycle performance is better than that of using tougher CMC / SBR and PVDF binders. However, CMC has high rigidity and low elongation at break (5-8%), which cannot completely eliminate the stress of volume expansion generated by silicon-based negative electrode materials during the cycle process. Therefore, cracks often appear during repeated cycles, resulting in significant battery capacity decay. Although SBR has certain elasticity, its bonding ability is weak, and the carbon-carbon double bond will degrade during the battery charging and discharging process, causing the binder to fail. In addition, during the deintercalation and intercalation of lithium ions in the battery, the charge easily activates CMC-Na to ionize, and the released sodium ions may exchange with lithium ions in the positive electrode material or electrolyte, leading to lithium deposition problems. Summary of the Invention

[0005] In order to overcome the deficiencies of the above-mentioned prior art, the present invention provides a modified carboxymethyl cellulose lithium negative electrode binder for lithium batteries. The modified carboxymethyl cellulose lithium is prepared by grafting acrylic acid monomers and sulfonic acid monomers onto the carboxymethyl cellulose main chain to copolymerize long chains, introducing additional carboxyl groups and sulfonic acid groups, and introducing cystine with a disulfide bond as a cross-linking agent and 2-(3,4-dihydroxyphenyl)ethylamine with a catechol group as a thickener. The obtained modified carboxymethyl cellulose lithium not only has a higher lithium content than ordinary carboxymethyl cellulose lithium, but also has enhanced bonding properties, improved toughness, and enhanced cycle performance.

[0006] The technical solutions for achieving the purpose of the present invention are as follows: A modified lithium carboxymethyl cellulose as a negative electrode binder for lithium batteries, wherein the preparation method of the modified lithium carboxymethyl cellulose comprises the following steps: S1. Grafting: Dissolve carboxymethyl cellulose in water, add acrylic acid monomer, sulfonic acid monomer, and initiator, and react with stirring at 40-60°C under anaerobic conditions for 2-4 hours. Neutralize with NaOH, and purify to obtain a CMC-Na graft copolymer. S2. Acidification: The CMC-Na graft copolymer was dispersed in an ethanol solution, hydrochloric acid was added, and the reaction was stirred for 2 to 4 hours, followed by washing with an ethanol solution and drying to obtain a CMC-H graft copolymer; S3. Lithiation: Disperse the CMC-H copolymer in an aqueous solution of ethanol. Add LiOH solution at 40-60°C to adjust the pH to 9-10 and stir for 2-10 hours. Then, add acetic acid to adjust the pH to 7-8. Filter, wash with ethanol solution, and dry to obtain a CMC-Li graft copolymer. S4. Cross-linking: The CMC-Li graft copolymer was dispersed in MES buffer, EDC and NHS were added to activate the carboxyl groups, cystine was added and stirred for 4-8 hours, and then 2-(3,4-dihydroxyphenyl)ethylamine was added and the reaction was continued for 4-8 hours. The mixture was washed with ethanol solution and dried to obtain modified lithium carboxymethyl cellulose.

[0007] Preferably, in step S1, the mass ratio of acrylic acid monomer, sulfonic acid monomer and carboxymethyl cellulose is (2-5): (0.5-1):1.

[0008] Preferably, the acrylic acid monomer is selected from at least one of acrylic acid and methacrylic acid; and the sulfonic acid monomer is selected from at least one of 2-acrylamido-2-methylpropanesulfonic acid and sodium p-styrenesulfonate.

[0009] Preferably, the initiator is ammonium persulfate and sodium bisulfite, and the amount of the initiator added is 0.5-1 wt% of the total weight of the monomers.

[0010] Preferably, the carboxymethyl substitution degree of the carboxymethyl cellulose is 0.7 to 1.4.

[0011] Preferably, the molar amount of cystine is 5-10 mol% of the total molar amount of carboxyl and sulfonic acid groups of the CMC-Li graft copolymer, and the molar amount of 2-(3,4-dihydroxyphenyl)ethylamine is 1-5 mol% of the total molar amount of carboxyl and sulfonic acid groups of the CMC-Li graft copolymer.

[0012] Preferably, the hydrochloric acid in step S2 is a hydrochloric acid solution with a mass concentration of 10-20 wt%, and the molar amount of the added hydrochloric acid is 2-4 times the total molar content of the carboxyl and sulfonic acid groups in the CMC-Na graft copolymer.

[0013] Preferably, the LiOH solution in step S3 is a LiOH solution with a mass concentration of 5 to 10 wt %, and the molar amount of the added LiOH is 1.5 to 3 times the total molar amount of the carboxyl groups and sulfonic acid groups of the CMC-Na graft copolymer.

[0014] Preferably, the ethanol solution is an ethanol aqueous solution with a volume concentration of 85-95%.

[0015] Beneficial effects

[0016] The present invention provides a modified carboxymethyl cellulose lithium negative electrode binder for lithium batteries, which has the following beneficial effects: (1) long carbon chains with carboxyl and sulfonic acid groups are grafted onto the linear chain segments of carboxymethyl cellulose, thereby increasing the content of anionic groups such as carboxyl and sulfonic acid groups of the carboxymethyl cellulose, thereby increasing the binding sites with the silicon surface and improving the bonding ability with the silicon negative electrode; (2) cystine with dynamic disulfide bonds is introduced as a cross-linking agent into the carboxymethyl cellulose and acrylic acid-sulfonic acid copolymer chain segments, thereby transforming the original linear brush structure into a cross-linked network structure, thereby improving the toughness and elongation at break of the carboxymethyl cellulose, and the dynamic disulfide bonds have a self-repairing effect. When the silicon negative electrode expands, the disulfide bonds break and release stress, thereby reducing the brittleness of the binder due to the volume expansion of the silicon negative electrode. The disulfide bonds reconnect when the volume is reduced, achieving dynamic self-repair and improving the cycle stability of the lithium battery; (3) 2-(3,4-dihydroxyphenyl)ethylamine with a catechol group is introduced as a thickener on the surface of carboxymethyl cellulose to further improve the thickening performance of carboxymethyl cellulose, and the use requirements of lithium battery binders can be met without the need to add additional styrene-butadiene rubber; (4) Lithium ions are used to replace traditional sodium ions. CMC-Li not only inherits the excellent binding properties of CMC-Na, but also has the ability to bind and release lithium ions. Compared with CMC-Na, it not only increases the number of lithium ions intercalated and deintercalated between the positive and negative electrodes, improves the specific capacity of the battery, but also improves the cycle efficiency and shortens the diffusion path of lithium between the electrodes. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 The diagram of the synthesis and structure of the modified lithium carboxymethyl cellulose of the present invention is as follows; Figure 2 IR spectra of carboxymethyl cellulose, CMC-Na graft copolymer and modified lithium carboxymethyl cellulose of Example 1. DETAILED DESCRIPTION

[0018] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the embodiments described are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making any creative efforts are within the scope of protection of the present invention.

[0019] In the examples, the experimental methods used are conventional methods unless otherwise specified, and the materials, reagents, etc. used are all commercially available unless otherwise specified.

[0020] The raw materials and equipment used in the embodiments and comparative examples are described below: Carboxymethyl cellulose: MW250000 (DS=0.9), 1500-3100 mPa.s, Changshu Weiyi Technology Co., Ltd. Acrylic acid: 95%, Shanghai Aladdin Biochemical Technology Co., Ltd.; Sulfonic acid monomer 1: 2-acrylamido-2-methylpropanesulfonic acid, 98%, purchased from MacLean; Sulfonic acid monomer 2: sodium p-styrene sulfonate, 90%, purchased from Maclean; Cystine: L-cystine, 99%, purchased from Maclean; 2-(3,4-dihydroxyphenyl)ethylamine: 98%, purchased from MacLean; LiOH: purchased from Maclean; MES buffer: pH 5.0, 0.5 M, purchased from Maclean; Unless otherwise specified, the components and raw materials used in the examples and comparative examples of the present invention are all commercially available raw materials, and the components and raw materials used in each parallel experiment are all of the same kind.

[0021] Example 1

[0022] A modified carboxymethyl cellulose lithium negative electrode binder for lithium batteries: homemade, the preparation method is as follows: S1. Grafting: Weigh 1g of carboxymethyl cellulose powder and dissolve it in 500ml of distilled water. Stir and form a transparent viscous solution. Then, introduce nitrogen for 6 hours to remove oxygen. Then, dissolve 0.5g of sodium p-styrene sulfonate in 10ml of distilled water and add it to the carboxymethyl cellulose solution together with 2.5g of acrylic acid, 0.3g of ammonium persulfate and 0.3g of sodium bisulfite. Stir continuously for 3h at 55℃ under nitrogen atmosphere. Add 3% NaOH solution to adjust the pH to 6. After the reaction, the product is precipitated and washed with anhydrous ethanol. The product was washed, then soaked in distilled water for 24 hours to remove the homopolymer, and vacuum dried to obtain a CMC-Na graft copolymer; the molar content of carboxyl and sulfonic acid groups in the CMC-Na graft copolymer was determined by the ash-alkali method, wherein the soluble salts in the CMC-Na graft copolymer were removed with a certain concentration of ethanol aqueous solution, and the product was dried and then calcined at high temperature in a muffle furnace. The residue was alkali metal oxide Na2O, which was dissolved in water and then added with excess sulfuric acid standard solution. The excess sulfuric acid was titrated with NaOH standard solution using methyl red as an indicator; S2. Acidification: The CMC-Na graft copolymer was dispersed in an ethanol solution, and 20% HCl was added at 35°C with stirring for 2 h. After filtering, the mixture was washed three times with ethanol solution and dried at 105°C to obtain a CMC-H graft copolymer. The molar amount of HCl added was three times the total molar content of carboxyl and sulfonic acid groups in the CMC-Na graft copolymer. S3. Lithiation: The CMC-H graft copolymer was dispersed in a 7% LiOH solution in ethanol and reacted at 50°C for 2 h. The molar amount of LiOH added was twice the total molar content of carboxyl and sulfonic acid groups in the CMC-H graft copolymer. After the reaction, acetic acid was added to adjust the pH to 7. The mixture was filtered and washed three times with ethanol and water solution. The mixture was then dried at 105°C to obtain a CMC-Li graft copolymer. S4. Cross-linking: The CMC-Li graft copolymer was dissolved in MES buffer, and EDC and NHS were added for activation for 30 minutes, with the amount of EDC and NHS added being 0.01wt% of the CMC-Li graft copolymer; L-cystine was added, and the molar amount of L-cystine was 5mol% of the total molar content of carboxyl and sulfonic groups of the CMC-H graft copolymer. The mixture was stirred and reacted for 6 hours under the conditions of light protection and nitrogen protection, and then 2-(3,4-dihydroxyphenyl)ethylamine solution was added, and the molar amount of 2-(3,4-dihydroxyphenyl)ethylamine was 1mol% of the total molar content of carboxyl and sulfonic groups of the CMC-Li graft copolymer. The mixture was stirred and reacted for 6 hours. After filtering, the mixture was washed with ethanol aqueous solution for 3 times and dried at 105°C to obtain modified carboxymethyl cellulose lithium. The modified carboxymethyl cellulose lithium was crushed using a crushing machine until it was powdery and passed through a 100-mesh sieve. The synthesis and structural diagram of the modified carboxymethyl cellulose lithium are shown in FIG. Figure 1 shown.

[0023] The ethanol solutions used in the above steps are all ethanol aqueous solutions with a volume concentration of 90%.

[0024] Infrared spectrometry was performed on carboxymethyl cellulose, CMC-Na graft copolymer, and modified lithium carboxymethyl cellulose using an IR / Nicolet 6700 infrared spectrometer. During sample preparation, a small amount of sample powder was mixed with KBr and ground. The ground sample should be transparent to ensure that light can pass through the sample. The wavelength range of the spectrometer was set to 4000 cm -1 ~500cm -1 ; The results are as follows Figure 2 shown.

[0025] Example 2

[0026] Compared with the preparation method of Example 1, the difference is that the molar amount of L-cystine in step S4 is 8 mol% of the total molar content of carboxyl groups and sulfonic acid groups in the CMC-Li graft copolymer.

[0027] Example 3

[0028] Compared with the preparation method of Example 1, the difference is that the molar amount of L-cystine in step S4 is 10 mol% of the total molar content of carboxyl groups and sulfonic acid groups in the CMC-Li graft copolymer.

[0029] Example 4

[0030] Compared with the preparation method of Example 1, the difference is that the molar amount of 2-(3,4-dihydroxyphenyl)ethylamine in step S4 is 3 mol % of the total molar content of carboxyl groups and sulfonic acid groups in the CMC-Li graft copolymer.

[0031] Example 5

[0032] Compared with the preparation method of Example 1, the difference is that the molar amount of 2-(3,4-dihydroxyphenyl)ethylamine in step S4 is 5 mol% of the total molar content of carboxyl groups and sulfonic acid groups in the CMC-Li graft copolymer.

[0033] Example 6

[0034] Compared with the preparation method of Example 1, the difference is that the sodium p-styrenesulfonate in step S1 is replaced by 2-acrylamido-2-methylpropanesulfonic acid.

[0035] Comparative Example 1 Compared with the preparation method of Example 1, the difference is that L-cystine is not added in step S4.

[0036] Comparative Example 2 Compared with the preparation method of Example 1, the difference is that 2-(3,4-dihydroxyphenyl)ethylamine is not added in step S4.

[0037] Comparative Example 3 Compared with the preparation method of Example 1, the difference is that no sulfonic acid monomer is added in step S1.

[0038] The modified lithium carboxymethyl cellulose prepared in the examples and comparative examples was subjected to the following tests, and the results are shown in Table 1: (1) Viscosity test: Weigh 5 g of modified carboxymethyl cellulose lithium sample dried at 105 ° C for 2 h, and prepare a 1% solution to the nearest 0.001 g; measure 495 mL of water to prepare a 1% CMC-Na solution) and put it into a wide-mouth bottle; place the wide-mouth bottle under the stirrer, turn on the stirrer power, and adjust the speed very slowly to 300 rpm, and slowly add the sample, making sure that all the sample is added to the solution. After the sample is completely added, slowly adjust the stirring speed to 900 rpm and stir for about 2 h (stir for high viscosity products for 3 to 4 h) until the sample is completely dissolved and evenly dissolved; place the wide-mouth bottle containing the prepared sample solution in a constant temperature water bath at 25 ° C. After keeping the temperature constant for at least 1 h, check the sample solution temperature. If the value is within the range of 25 ± 0.2 ° C, use a DV2T viscometer for the test.

[0039] (2) Peel test: The evaluation of adhesion performance is usually carried out through a peel strength test. When performing the peel strength test, the pre-prepared electrode sheet is first pasted onto the aluminum plate substrate, and then firmly adhered to the electrode-coated surface with 3M tape. The specific operation is to stick a 120×25mm electrode sample on 3M transparent tape, stick it on the coating and pull it at a 180° angle. The force required to pull the tape at a fixed speed of 100 mm / min was recorded. The electrode sheet was prepared by weighing a silicon oxide anode, conductive carbon black, single-walled carbon nanotubes, and modified carboxymethyl cellulose lithium binder in a mass ratio of 95:1:0.05:3.95. The modified carboxymethyl cellulose lithium was dissolved in a solvent, and solvent was added as needed based on the solution viscosity. The weighed silicon oxide anode, conductive carbon black, and single-walled carbon nanotubes were ground in an agate mortar and pestle. After mixing thoroughly, the dissolved modified carboxymethyl cellulose lithium was added. An appropriate amount of solvent was added again based on the slurry viscosity. The beaker was sealed with plastic wrap and stirred on a stirrer for 12 hours. The stirred electrode slurry was then coated on copper foil that had been wiped with anhydrous ethanol and dried to produce the electrode sheet. The electrode sheet was then dried in a 50°C oven for 12 hours to obtain the electrode sheet.

[0040] (3) Cycle capacity retention rate: The positive electrode material (active material is NCM811) and the negative electrode material (silicon oxide negative electrode, conductive carbon black, single-walled carbon nanotubes and modified carboxymethyl cellulose lithium binder with a mass ratio of 95:1:0.05:3.95) are stirred, coated, rolled and die-cut to obtain positive electrode sheets and negative electrode sheets respectively; the obtained positive electrode sheets, negative electrode sheets and separators (12+4 ceramic coated separators) are stacked, spot welded, packaged and baked, and the electrolyte (solute is LiPF6, solvent is EC and DMC with a mass ratio of 4:1) is injected, and then the electrolyte is injected, allowed to stand, formed, aged and separated in sequence to obtain a lithium-ion battery; the obtained lithium-ion battery is cycled at 1C / 1C for 500 weeks between 2.75 and 4.2V to test its capacity retention rate.

[0041] Table 1 Performance test of examples and comparative examples

[0042] It can be seen from Examples 1 to 3 that as the amount of cystine added increases, the crosslinking density of lithium carboxymethyl cellulose increases, the viscosity increases, and the cycle capacity retention rate improves, but the peel strength tends to first increase and then decrease. This is because when the crosslinking density is too large, the rigidity of the material increases and the flexibility decreases, and stress concentration is more likely to occur during the peeling process, resulting in local damage to the material, thereby reducing the peel strength.

[0043] It can be seen from Examples 1 to 3 that as the amount of 2-(3,4-dihydroxyphenyl)ethylamine added increases, the viscosity and peel strength of lithium carboxymethyl cellulose increase, and the cycle capacity retention rate also improves.

[0044] It can be seen from Examples 1, 6 and Comparative Example 3 that the introduction of sulfonic acid groups by grafting acrylic acid-sulfonic acid copolymers on the side chains of carboxymethyl cellulose can improve the bonding ability and cycle capacity retention rate of the modified carboxymethyl cellulose. This may be because the high ionic conductivity and anti-expansion ability of the sulfonic acid group can significantly improve the cycle life of the silicon negative electrode.

[0045] The preferred embodiments of the present invention disclosed above are intended only to help illustrate the present invention. These preferred embodiments do not exhaustively describe all details, nor do they limit the present invention to the specific embodiments described. Obviously, many modifications and variations are possible based on the content of this specification. These embodiments are selected and described in detail in this specification to better explain the principles and practical applications of the present invention, thereby enabling those skilled in the art to better understand and utilize the present invention. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A modified carboxymethyl cellulose lithium negative electrode binder for lithium batteries, characterized in that: The preparation method of the modified lithium carboxymethyl cellulose comprises the following steps: S1. Grafting: dissolving carboxymethyl cellulose in water, adding acrylic acid monomer, sulfonic acid monomer and initiator, stirring and reacting at 40-60°C for 2-4h under anaerobic conditions, adding NaOH for neutralization, and purifying to obtain CMC-Na graft copolymer; S2. Acidification: The CMC-Na graft copolymer was dispersed in an ethanol solution, hydrochloric acid was added, stirred for 2 to 4 hours, washed with an ethanol solution, and dried to obtain a CMC-H graft copolymer; S3. Lithiation: Disperse the CMC-H copolymer in an aqueous solution of ethanol, add LiOH solution at 40-60°C to adjust the pH to 9-10 and stir for 2-10 hours, then add acetic acid to adjust the pH to 7-8, filter, wash with ethanol solution, and dry to obtain a CMC-Li graft copolymer; S4. Cross-linking: Disperse the CMC-Li graft copolymer in MES buffer, add EDC and NHS to activate the carboxyl group, add cystine and stir to react for 4-8 hours, then add 2-(3,4-dihydroxyphenyl)ethylamine and continue to react for 4-8 hours, wash with ethanol solution, and dry to obtain modified carboxymethyl cellulose lithium.

2. The modified carboxymethyl cellulose lithium negative electrode binder for lithium batteries according to claim 1, characterized in that: In step S1, the mass ratio of acrylic acid monomer, sulfonic acid monomer and carboxymethyl cellulose is (2-5): (0.5-1):

1.

3. The negative electrode binder for lithium battery of modified carboxymethyl cellulose lithium according to claim 1, characterized in that: The acrylic acid monomer is selected from at least one of acrylic acid and methacrylic acid; the sulfonic acid monomer is selected from at least one of 2-acrylamide-2-methylpropanesulfonic acid and sodium p-styrenesulfonate.

4. The negative electrode binder for lithium battery of modified carboxymethyl cellulose lithium according to claim 1, characterized in that: The initiators are ammonium persulfate and sodium bisulfite, and the added amount of the initiators is 0.5-1 wt % of the total weight of the monomers.

5. The modified carboxymethyl cellulose lithium negative electrode binder for lithium batteries according to claim 1, characterized in that: The carboxymethyl substitution degree of the carboxymethyl cellulose is 0.7-1.

4.

6. The modified carboxymethyl cellulose lithium negative electrode binder for lithium batteries according to claim 1, characterized in that: The molar amount of cystine is 5-10 mol% of the total molar amount of carboxyl and sulfonic acid groups of the CMC-Li graft copolymer, and the molar amount of 2-(3,4-dihydroxyphenyl)ethylamine is 1-5 mol% of the total molar amount of carboxyl and sulfonic acid groups of the CMC-Li graft copolymer.

7. The negative electrode binder for lithium battery of modified carboxymethyl cellulose lithium according to claim 1, characterized in that: The hydrochloric acid in step S2 is a hydrochloric acid solution with a mass concentration of 10-20wt%, and the molar amount of the added hydrochloric acid is 2-4 times the total molar amount of the carboxyl group and the sulfonic acid group of the CMC-Na graft copolymer.

8. The negative electrode binder for lithium battery of modified carboxymethyl cellulose lithium according to claim 1, characterized in that: The LiOH solution in step S3 is a LiOH solution with a mass concentration of 5-10wt%, and the molar amount of added LiOH is 1.5-3 times the total molar amount of carboxyl groups and sulfonic acid groups of the CMC-Na graft copolymer.

9. The negative electrode binder for lithium battery of modified carboxymethyl cellulose lithium according to claim 1, characterized in that: The ethanol solution is an ethanol aqueous solution with a volume concentration of 85-95%.

Citation Information

Patent Citations

  • Simulated mussel protein environment-friendly lithium ion battery adhesive

    CN103342974A

  • Adhesive for lithium ion battery

    CN105504169A

  • Modification method and application of silicon-based binder for negative electrode material of lithium ion battery

    CN112322223A

  • Adhesive for lithium ion battery as well as preparation method and application of adhesive

    CN115911391A

  • High-viscosity carboxymethyl cellulose as well as preparation method and application thereof

    CN117126335A

Cited By

  • Three-dimensional conductive network carboxymethyl cellulose composite binder and preparation method thereof

    CN120173536A

  • Lithium battery adhesive and preparation method thereof

    CN120424606A

  • Negative electrode binder, negative electrode plate and battery

    CN122051235A